Climate Change Adaptation Frameworks for Port Infrastructure and Workforce Safety: Integrated Risk Management and Human Resource Resilience in Indonesian Maritime Operations - Rosna Yuherlina Siahaan (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
This research investigates climate change adaptation frameworks for Indonesian port infrastructure and workforce safety through integrated risk management approaches addressing physical facility resilience and human resource protection. Through qualitative analysis involving 37 stakeholders including port authorities, terminal operators, marine engineers, climate scientists, occupational health specialists, and port workers, this study examines how climate threats including sea level rise, extreme weather, flooding, and heat stress affect both port operations and worker safety requiring coordinated adaptation strategies. Results demonstrate that integrated frameworks can reduce climate-related operational disruptions by 50-70%, decrease worker heat illness by 60-80%, improve emergency response effectiveness by 55-75%, and enhance infrastructure resilience by 45-65% when combining physical hardening with workforce protection measures. Key challenges include immediate infrastructure damage (ports already experiencing 3-8 annual flooding shutdowns), worker heat illness epidemic (150+ cases in 2023 with 300% increase), investment decision urgency (15-25 billion infrastructure commitments 2024-2030), and organizational coordination across fragmented stakeholders. Findings reveal that successful climate adaptation requires holistic sociotechnical approaches treating ports as integrated human-infrastructure systems where worker safety and facility resilience prove inseparable, supporting Indonesia's maritime economic security and coastal community welfare through comprehensive climate risk management.